Development of an Android Based Personal Financial Management Application for Financial Monitoring and Student Expense Notifications - Rizki Alfa Reza; Yuyun Khairunisa; Nur Rahmansyah (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
This development was carried out because many students still experience difficulties in managing their finances, resulting in waste and uncontrolled financial conditions. This is usually caused by a lack of awareness in financial recording and the absence of adequate tools to monitor income and expenses regularly. As a result, students often experience difficulties in meeting daily needs or sudden needs. The purpose of this research is to develop an Android-based personal financial management application to help students manage their finances better, in a structured, and efficient manner. With this application, it is hoped that students can make financial recording easier and more structured. The research was conducted by collecting data through observation and interviews to identify user needs in managing finances and understand the problems often faced by students in daily financial activities. The method used in this development is the Agile method, using the Scrum framework, which allows the development process to be carried out in stages and flexibly so that it can adapt to user needs. This application was developed on the Android platform by utilizing Firebase Authentication which is used as a security system to maintain the confidentiality of user data, while the Firebase Cloud Firestore service helps in data storage so as to reduce the risk of data loss. Black Box Testing showed that all application features functioned successfully according to system requirements. Based on usability testing using the System Usability Scale (SUS) involving 22 respondents, the application obtained a score of 79.09 which indicates that the application has good usability and is acceptable to users. Based on these results, the developed application can help students better manage their finances.